The Solvency Level of Sharia Insurance Companies in Indonesia (A Critical Analysis Study) - Ai Fitri Nurlatifah; Rossje V Saputri (AJIS: Academic Journal of Islamic Studies, 2022)
This study aimed to determine the determinants of the solvency level of Islamic insurance companies in Indonesia. The independent variables used in this study are BOC, BOD, SSB and SOC, tabarru’ funds, contribution, investment growth, RBK, inflation and GDP. While the control variables used are size, volume of capital, leverage and liquidity as control variables. The sample in this study used a purposive sampling technique, namely 43 companies with a total number of 215 observations. The observation period was from 2017-2021 and the data analysis method used the data regression panel which was processed using E-views 12 software. Based on the test results, it was shown that simultaneously BOC, BOD, SSB and SOC, tabarru’ funds, contribution, investment growth, RBK, inflation and GDP affect the solvency level. partially, the board of commissioners, tabarru’ funds and investment growth have a positive effect, while SOC, contribution and RBK have a negative effect on the solvency level of Islamic insurance companies in Indonesia. Meanwhile, BOD, SSB, Inflation and GDP have no effect on the level of solvency.